Analysis of phenolics from Centella asiatica and Vernonia amygdalina and their role as antibacterial and antioxidant compounds / Suzanna a/p Edgar - Edgar, Suzanna (2014)
Six species of Malaysian medicinal plants were selected on the basis of their known medicinal values. The plants chosen were Aloe vera - leaf and pulp, Azadirachta indica - leaf, Carica papaya - leaf, Centella asiatica - whole plant, Hymenocallis speciosa - leaf, tuber and root, Vernonia amygdalina - leaf and stem. Aqueous and ethanolic extract of the plant tissues were tested for their antimicrobial properties against five test microorganisms. Of the six plants tested, the aqueous and ethanolic extract of C. asiatica (whole plant) exhibited highly significant antimicrobial activity against the bacterial strains while the ethanolic extract of Vernonia amygdalina (leaf) showed distinct inhibition only towards B. cereus. C. asiatica and V. amygdalina were selected as candidates for further evaluation of their medicinal properties. Ammonium sulphate precipitation was conducted to determine if antimicrobial activity was due to peptides present in the plant. The antimicrobial activity for ethanolic plant extracts was observed in the supernatant with their pellet showing insignificant antimicrobial activity. The highest antimicrobial activity was observed in the ammonium sulphate supernatant of C. asiatica against S. aureus and B. cereus. Since phenolic compounds are responsible for their antimicrobial and antioxidant properties, they were investigated in C. asiatica and V. amygdalina. Total phenolic content (TPC) of plant extracts were determined with Folin-Coicalteu assay. In C. asiatica, the TPC of the ethanolic extract was the highest 4.006 ± 0.032 mg GAE/g d.w followed by methanolic extracts 3.346 ± 0.029 mg GAE/g d.w and aqueous extracts 1.120 ± 0.063 mg GAE/g d.w. In V. amygdalina, the TPC was highest in methanolic extract 1.168 ± 0.101 mg GAE/g d.w, followed by aqueous extract and ethanolic extract had the lowest TPC. Abstract iii The antioxidant properties of the extracts were determined by DPPH radical scavenging assay and FRAP. Using the DPPH assay, ethanolic extract of C. asiatica showed high radical scavenging activity whereas the lowest activity was observed in the aqueous extracts. All three extracts of V. amygdalina showed weak radical scavenging activity. Using the FRAP assay, reducing capability of C. asiatica and was observed as methanol > ethanol > aqueous > ascorbic acid and the reducing capability of V. amygdalina extracts was observed as methanol > aqueous > ethanol > ascorbic acid. Protective effect of the plant extracts were tested against hydrogen peroxide induced haemolysis in vitro. The ethanolic and methanolic extracts of C. asiatica and V. amygdalina showed strong protective effect against hydrogen peroxide. Biologically active phenolic compounds present were elucidated with reverse-phase high performance liquid chromatography (RP-HPLC), liquid chromatography mass spectroscopy (LC-MS) and fourier transform infrared spectroscopy (FT-IR). RP-HPLC of C. asiatica methanolic extract presented two major compounds: chloramphenicol and benzoic acid. The identification of these compounds was confirmed by FT-IR analysis. The phenolic compounds in V. amygdalina were not well separated hence LC-MS was done. Analysis by LC-MS identified thirty eight phenolic compounds in C. asiatica and forty in V. amygdalina including gallic acid derivatives, hydroxybenzoic acid, hydroxycinnamic acid, flavonoids, purine alkaloids and phenolic terpenes and lignins. Amongst them, the presence of phloridzin which is known for its antidiabetic properties was detected in the methanolic extract of V. amygdalina.